Structure and Function of the LRBA Protein - BARIŞ, SAFA (My University, 2024)
Beige and Chediak (BEACH) domain-containing protein (BDCP) family proteins are large cytoplasmic adaptor proteins associated with endosomal and lysosomal recycling and degradation pathways. These proteins have C-terminal PH, Beach and WD40 domains, whose structures are solved or can be predicted using recently developed algorithms such as Alphafold. Family members such as LRBA, LYST and NBEAL2 are implicated in human disease. LRBA was shown to be responsible for the re-shuttling of the T-cell co-inhibitory receptor CTLA4 back to the plasma membrane after internalization and lack or mutation of LRBA results in surface deficiency of CTLA4 in regulatory and activated T lymphocytes. The large molecular size of these proteins indicates that they may have pleiotropic functions in the immune system and beyond. Sequence and domain structure similarities between the proteins suggest that a level of redundancy may be present, which could potentially result in new therapeutic avenues.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; Chédiak Higashi syndrome; common variable immunodeficiency; CTLA4; immune dysregulation; LRBA; LYST